2012
DOI: 10.1007/s10140-012-1098-0
|View full text |Cite
|
Sign up to set email alerts
|

Head computed tomography utilization and intracranial hemorrhage rates

Abstract: Utilization of computed tomography scans (CTs) has increased dramatically in emergency departments in the USA. This study aimed to retrospectively determine the yield of CTs among all patients that received a CT of the head from 2001 to 2007, which is adjusted for patient volume. For secondary endpoints, we examined the yield of CT of the head for the following hemorrhages: (1) intracerebral, (2) subarachnoid, (3) subdural, and (4) epidural. In 2001, 3.3 head CTs were performed per 100 patients seen. This incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…Therefore, we believe that our findings are valid in that the trend to decrease abdominal CT utilization in our cohort is more marked. Our results differed from Lee et al, who reported a 60% increase in head CT use between 2003 and 2007 while the yield for positive results remained constant [41]. The difference is likely due to the fact that Lee's study reported head CT use in all patient populations while our study involved only admitted trauma patients.…”
Section: Discussioncontrasting
confidence: 91%
“…Therefore, we believe that our findings are valid in that the trend to decrease abdominal CT utilization in our cohort is more marked. Our results differed from Lee et al, who reported a 60% increase in head CT use between 2003 and 2007 while the yield for positive results remained constant [41]. The difference is likely due to the fact that Lee's study reported head CT use in all patient populations while our study involved only admitted trauma patients.…”
Section: Discussioncontrasting
confidence: 91%
“…However, increased rates of CT use can expose patients to excessive levels of radiation and society to higher medical costs. One retrospective study that reviewed brain CT utilization in a single ED found that the rate of brain CT use had increased by 60% over a 7-year period; however, the diagnostic yield for intracranial hemorrhage had remained constant at approximately 3% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral aneurysms are being detected more frequently due in large part to an increase in both availability and utilization of cross-sectional brain imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI). 56 Additionally, screening for intracranial vascular lesions prior to organ transplantation has become more common in recent years. 57 Unlike ruptured aneurysms, the unruptured aneurysm presents a unique dilemma as to which lesions are best suited for treatment as opposed to observation.…”
Section: Unruptured Aneurysmsmentioning
confidence: 99%